Technology Transfers and Knowledge Managementin Developing Economies:Case Study of an Indonesian Manufacturer - Wahyudi Wibowo (Journal of Entrepreneurship, Management and Innovation)

(untitled)
International technology transfers are crucial for developing economies since they may operate as one of the key drivers in the economies’ development path. Previous studies have acknowleged some channels of technology transfers for developing economies. Nevertheless, the precise mechanisms of how the technology transfers would occur and take effect in each of the recipient economies and their domestic companies are still to be explored. Furthermore, understanding domestic companies knowledge management is important since it would determine the absorptive capacity of the company toward advanced foreign technologies. This study uses a case of technologically intermediate-level Indonesian manufacturer to show evidence of international technology transfers and their impacts on the development of indigenous technological capabilities of the domestic company, as well as to examine the company’s knowledge management. This study confirmed some benefits of international technology transfers for the domestic company, especially through the major mechanisms of technical license assistances, capital goods imports, turnkey projects, technical consultancies, backward-vertical flows of foreign direct investment, and participation in overseas markets. However, the impacts toward the domestic company’s technological capabilities were generally at intermediate level. This implies that the domestic company needs to spend more investments on in-house R&D activities and to improve its knowledge management systems.